PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI HOTEL EMERALD GARDEN MEDAN - RIANTO MANURUNG (LP2MTBM MAKARIOZ, 2020)
The research aims to test the influence of work discipline and work environment on the employee performance of theEmerald Garden Hotel. The type of research used is quantitative research. The study used the census method with thequestionnaire instrument, the sampling technique of the study using probability sampling technique where samples of morethan 100 people, were calculated with Slovin formula so that the sample was 75 people. Processing techniques and dataanalysis using validity tests, reliability tests, classical assumption tests, descriptive analysis, cross tabulation, multiple linearregression analyses, and coefficient of determination analysis. The results of the study showed that individual disciplineshave significant effect on employees ' performance and the working environment is significant and is the dominant variable toemployee performance. The results of the test together with the work discipline and working environment have significanteffect on the employees ' performance of Hotel Emerald Garden Medan. The value of RSquare is 0.741 or 74.10%, whichmeans that the research variable contributes greatly to the contribution of the employee's performance of Hotel EmeraldGarden Medan by 74.10% while the remaining 25.90% is influenced by other factors outside this research.